Enhanced thrombin generation in plasma of severe thrombocytopenic patients due to rFVIIa - Novak, M.; Hiden, M.; Rehak, T.; Rosenkranz, A.; Zebisch, A.; Sill, H.; Klaschka, S.; Muntean, W. (Hämostaseologie, 2008)
RFVIIa-enhanced thrombin generation has been shown to be dependent on platelets. In previous work we have shown that addition of monocytes and rFVIIa to microparticle free plasma causes a distinct thrombin generation. The aim of our study has been to examine whether there is enough surface provided by microparticles in thrombocytopenic plasma to allow an effect of rFVIIa. Patients, methods: Thrombin generation was measured in platelet rich plasma (PRP) and microparticle free plasma (MFP) of thrombocytopenic haemato-oncological patients with and without addition of rVIIa by means of calibrated automated thrombography. Microparticles were analyzed in PRP by FACS flow cytometry. Results: Microparticle free plasma showed no thrombin generation with or without addition of rFVIIa. Addition of rFVIIa to PRP of thrombocytopenic patients led to a significant shortening of lag time and time to peak in thrombin generation, while ETP and peak remained unchanged. Conclusion: Our results show that even in plasma of severe thrombocytopenic patients enough surface may be provided by microparticles to allow an enhancement of thrombin generation by rFVIIa.
Keywords: Thrombin generation; rFVIIa; thrombocytopenia; microparticles